PENERAPAN STRATEGI PEMBELAJARAN PREDICT-OBSERVE-EXPLAIN (POE) UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN SEJARAH SMA KELAS X IPS SMAN 2 PERANAP - Faisal, Faisal; Isjoni, Isjoni; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low student learning outcomes in the history subjects of class X IPS at SMAN 2 Peranap. Based on these problems, the formulation of the problem in this study is whether the application of the predict-observe-explain (POE) learning model can improve the learning outcomes of class X IPS students of SMA Negeri 1 Peranap. The purpose of this study is to find out the activities of teachers and students in the implementation of the learning process by using the predict-observe-explain (POE) model and to determine the effect of this learning model on learning outcomes of students of class X IPS SMA Negeri 2 Peranap on historical subjects. This research was conducted in two cycles, in the first cycle the learning outcomes of students reached 81.8% classical completeness and increased in the second cycle reached 100%. Based on the results of these studies it can be concluded that the application of the predict-observe-explain (POE) learning model can improve student learning outcomes in the history lesson of the X IPS class at SMA Negeri 2 Peranap.Key Words: Learning strategy predict-observe-explain (POE), Learning Outcomes